Testing the Efficacy of the SANE-SART Programs in Kansas, Massachusetts, and New Jersey, 1997-2001 - Nugent-Borakove, M. Elaine ([Verlag nicht ermittelbar], 2008)
The purpose of the study was to explore the impact of interventions by Sexual Assault Nurse Examiners/Sexual Assault Response Teams (SANE/SART) on the judicial process. The goal was to test the efficacy of SANE/SART programs as a tool in the criminal justice system. The American Prosecutors Research Institute and Boston College tested the hypotheses that SANE/SART exams increase arrest and prosecution rates. The researchers collected case information from SANE/SART, police, and prosecution files in three jurisdictions: Monmouth County (Freehold), New Jersey, Sedgwick County (Wichita), Kansas, and Suffolk County (Boston), Massachusetts. At each study site, the project team randomly selected up to 125 sexual assault cases in which there was a SANE or SART intervention and 125 cases in which there was no SANE/SART intervention from cases that were opened and closed between 1997 and 2001. Comparisons were sought between SANE/SART cases (both SANE only and SANE/SART combined) and non-SANE/SART cases to determine if the intervention predicted the likelihood of certain criminal justice system outcomes. These outcomes included identification/arrest of a suspect, the filing of charges, case disposition, type of penalty, and length of sentence. In addition, researchers collected information on a number of other variables that could impact or mitigate the effect of SANE/SART interventions and case outcomes. The researchers abstracted information from case files maintained by SANE programs, police incident/arrest reports, and prosecution files during intensive five-day site visits. Three standardized records abstraction forms were developed to collect data: (1) the incident form was designed to collect data from police reports and the prosecution files about the actual sexual assault, (2) the case abstraction form was designed to collect prosecution data and case outcome data from the prosecutors' case files, and (3) the SANE/SART data collection form collected information from the SANE/SART files about the SANE/SART intervention. Specific information regarding the evidence collected during the victim's exam, nature of the assault, evidence/forensic kits collected, victim's demeanor, weapon(s) used, number of assailants, and the victim/offender relationship were collected.